An Aqueous Territory Sailor Geographies and New Granada's Transimperial Greater Caribbean World - Bassi, Ernesto (Duke University Press, 2016)
In 'An Aqueous Territory' Ernesto Bassi traces the configuration of a geographic space he calls the transimperial Greater Caribbean between 1760 and 1860. Focusing on the Caribbean coast of New Granada (present-day Colombia), Bassi shows that the region's residents did not live their lives bounded by geopolitical borders. Rather, the cross-border activities of sailors, traders, revolutionaries, indigenous peoples, and others reflected their perceptions of the Caribbean as a transimperial space where trade, information, and people circulated, both conforming to and in defiance of imperial regulations. Bassi demonstrates that the islands, continental coasts, and open waters of the transimperial Greater Caribbean constituted a space that was simultaneously Spanish, British, French, Dutch, Danish, Anglo-American, African, and indigenous.